A fluorescence 'turn-on' chemodosimeter for the specific detection of Pd2+ by a rhodamine appended Schiff base and its application in live cell imaging. Issue 28 (6th July 2017) - Bhanja, Anup Kumar; Mishra, Snehasis; Das Saha, Krishna; Sinha, Chittaranjan
Abstract : Allylether-Rhodamine selectively invites Pd 2+ from mixture of other cations and Pd(0) in H2 O-MeCN medium and exhibits maroon emission due to C(allyl)-O bond cleavage and opening of spirolactam ring. The LOD is 50 nM at pH 7. Imaging Pd 2+ species in living cells under physiological conditions is achieved. Abstract : A new rhodamine based allyl-ether Schiff base (RD) was spectroscopically characterized and used as a colorimetric and fluorimetric sensor. RD acts as turn-on highly selective fluorescent chemosensor for Pd(ii ) from only a mixture of Pd(0) and Pd(ii ) in the presence of 25 other cations in aqueous-acetonitrile medium. The mechanism for Pd(ii ) sensing with RD involves Pd(ii )-triggered terminal (C–O)-allyl bond cleavage followed by opening of the spirolactam ring. Pd(ii ) is allylphilic and the (rhodamine)O-allyl moiety selects Pd(ii ) from the mixture (Pd(0) + Pd(ii )), and a fluorescence enhancement is observed. The proposal has been supported by spectroscopic data (FTIR, 1 H NMR, 13 C NMR, and mass spectroscopy). It is again supported by examining the Pd(ii ) selectivity of an non-allylated rhodamine appended iminephenol (RD′), which failed to selectively detect Pd(ii ). Hence, the presence of the allylether is mandatory in the fluorogenic motif for Pd(ii ) selectivity. The limit of detection (LOD) of Pd(ii ) by RD is 50 nM at pH 7.4. Fluorescence microscopic studies help in imaging the cellular uptake of Pd 2+ at the nM level in the HCT116 (Human colorectal carcinoma) cell line.